Spread of Multi-Antibiotic-Resistant Health-Care Pathogens in Hospitals to Treat COVID-19 Patients - A. E. Goncharov; L. P. Zueva; A. S. Mokhov; V. V. Kolodzhieva; A. A. Meltser; M. V. Smirnova; T. V. Khavlina; E. A. Orishak (Эпидемиология и вакцинопрофилактика)
Relevance. The COVID-19 pandemic has led to significant overloads in the work of health systems in many countries, a shortage of beds and staff, which contributes to a decrease in adherence to measures to prevent and control nosocomial infections, which can significantly worsen the course of viral pneumonia. Aim. To assess the possibility of the formation of hospital strains of multidrugresistant microorganisms in hospitals repurposed to provide medical care to patients with COVID-19. Materials and methods. The study included patients with severe and moderate forms of COVID-19 (ICD codes U07.1, U07.2), who were admitted to two large hospitals repurposed for the treatment of this infection. The data of microbiological studies of the biomaterial associated with the respiratory tract (sputum, bronchoalveolar lavage, tracheal aspirates) obtained from 1101 patients from May to January 2021 were analyzed using a combination of molecular genetic methods (RAPD-PCR, detection of integrons and the carbapenemase gene bla NDM.), and molecular typing of carbapenem-resistant strains of Klebsiella pneumoniae and Acinetobacter baumannii was carried out. Results. It was found that carbapenem resistant gram-negative bacteria predominate in the structure of the nosocomial microbiota of the respiratory tract of patients with COVID-19 in both hospitals. Based on molecular typing made the wide distribution of several genetic lines of integron-positive carbapenem resistant Klebsiella pneumoniae and Acinetobacter baumannii was detected. Conclusions. The COVID-19 pandemic has exacerbated the spread and circulation of bacteria with multiple antibiotic resistance in hospitals. This study has demonstrated the possibility of the formation of hospital strains of nosocomial infections in COVID-19 hospitals, which justifies the need to improve infection control measures in the context of a new coronavirus infection pandemic.